2012
DOI: 10.1007/s11427-012-4283-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of human amniotic epithelial cell transplantation on double-transgenic mice co-expressing APPswe and PS1ΔE9-deleted genes

Abstract: Human amniotic epithelial cells (HAECs), which exhibit characteristics of embryonic and pluripotent stem cells, could be utilized for cell therapy without legal or ethical problems. Double-transgenic (TG) mice (n=20) and wild-type (WT) mice (n=20) were randomly assigned to two groups, respectively. The transplantation group was treated with HAECs and the control group with PBS. A six-radial arm water maze was used to assess spatial memory. Immunofluorescence was utilized to track HAEC survival. Immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Our findings demonstrated that cognitive function improved significantly as the Aβ level decreased. Intracerebroventricular transplantation of hAMMSCs increased acetylcholine concentration and the number of hippocampal cholinergic neurites in AbPP/PS1 transgenic AD mice (34). Following hAMMSC injection, the number of ED1-positive phagocytic microglial cells associated with Aβ plaques was enhanced, the expression levels of proinflammatory cytokines were decreased, and those of anti-inflammatory cytokines were increased (35).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated that cognitive function improved significantly as the Aβ level decreased. Intracerebroventricular transplantation of hAMMSCs increased acetylcholine concentration and the number of hippocampal cholinergic neurites in AbPP/PS1 transgenic AD mice (34). Following hAMMSC injection, the number of ED1-positive phagocytic microglial cells associated with Aβ plaques was enhanced, the expression levels of proinflammatory cytokines were decreased, and those of anti-inflammatory cytokines were increased (35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, transplanted hAECs produce neurotrophic substances and stimulate repair and regeneration of host neurons in a primate model of spinal cord injury (Sankar and Muthusamy, 2003). In addition, hAECs transplanted into the cerebral lateral ventricle of a transgenic mouse model of Alzheimer's disease were found to rescue damaged cholinergic neurons (Xue et al, 2012). The authors reported that hAEC treatment increased the number of cholinergic neurons, as well as the level of acetylcholine produced by these cells, which was suggested to be largely responsible for the reversal of cognitive decline in this animal model.…”
Section: The Potential For Stem Cell Therapy Following Strokementioning
confidence: 99%
“…In our recent studies, transplantation of human NSCs overexpressing choline acetyltransferase (ChAT) gene improved the learning and memory functions of AD model and aging animals by increasing acetylcholine (ACh) concentration [1719]. Notably, brain and reproductive organs including placenta contain high levels of ChAT, and amniotic membrane epithelial stem cells (AMESCs) and amniotic membrane‐derived mesenchymal stem cells (AMMSCs) express ChAT and secrete ACh [2022]. Indeed, transplantation of AMESCs and AMMSCs ameliorated spatial memory deficit in AD model animals [22, 23].…”
Section: Introductionmentioning
confidence: 99%